Bioremediation of oil contaminated wastewater using mixed culture - Husni, Basharudin (2008)
The objective of this research is to study the effect of the oil degradation based on the different temperature and different oil concentration using mixed culture from domestic wastewater. The evaluation is based on microorganism activities by the rate of oil degradation. The inoculum used was a mixed culture containing oil-degrading microorganism isolates from the sewage system located at Perak. For the wastewater used was artificially made by using palm oil as carbon substrate and medium for the microorganism to study the effect of temperature and oil concentration. Wastewater was treated by using the inoculum of the mixed culture for 20 days of incubation time and temperature range from 10oC to 60oC. From the experiment, it was observed that, the rate of oil degradation is was high at mesophilic condition which was at temperature of 30oC resulted of 4.722 g from 10 g of oil have been degraded during the incubation time. The result also showed that, oil concentration at high value can limit the rate of oil degradation. It showed that rate of oil degradation was inversely proportional to the concentration of oil. From this study, it is shown that the effectiveness of oil degradation is increased by increasing in temperature and the optimum temperature in this study was 30oC at low oil concentration.